Keeping It Literal: The Economy of the Song of Songs - Roland Boer (Journal of Hebrew Scriptures, 2009)
This essay seeks the underlying worldview of the Song of Songs. It does so in three steps. Firstly, over against the widespread assumption that the metaphors of the Song of Songs refer to human erotic love, or indeed the older assumption that they are allegories for the relations between God and Israel, or God and the Church, this article asks what happens when we break such metaphoric connections. In other words, what happens if we take the metaphors at face value? Secondly, once the metaphors are freed from their links with human erotic love, they take on a life of their own, one of fecund and fertile nature. The third step involves an exploration of what the worldview of such a fecund nature might be. My suggestion is that it may be understood as a utopian element – nature producing freely and of its own accord – of what I call the sacred economy.